Extraction of natural pigments from fruits and vegetables wastes to reduce food waste problem - Wong, Kwong Long (2022)
Increased food wastage problem during COVID-19 pandemic, limitations on the conventional food waste management approaches and consumers’ concerns on artificial colourants have induced the urge to recover valuable components from food waste as an approach for food waste valorisation practice. Therefore, recovery of natural pigments from fruits and vegetables wastes was introduced to address these issues. This study aims to analyse the factor that affects the stability of the pigments and compare the novel extraction techniques and determine the possibility of implementing green extraction techniques. The targeted pigments include water soluble pigments (anthocyanins and betalains) and lipid soluble pigments (carotenoids), whereas the novel extraction technologies being compared are microwaveassisted extraction (MAE), ultrasound-assisted extraction (UAE), pulsedelectric field (PEF) extraction, supercritical fluid extraction (SFE) and enzyme-assisted extraction (EAE). The stability assessment of the pigments consists of four main factors; pH, temperature, light exposure and oxygen concentration. The outcomes of stability assessment showed that anthocyanins were highly sensitive to pH change, betalains were thermolabile and carotenoids were highly destructed under strong light exposure and oxygen-rich atmosphere. The results of comparison between the novel extraction techniques have manifested that PEF extraction was the best technique used to recover water soluble pigments due to its highest extraction yield of anthocyanins and betalains, non-thermal approach and insignificant environmental impacts. In contrast, SFE exhibited the highest potential in extracting lipid soluble pigments due to its non-polar nature, greatest extraction yield of carotenoids and created no environmental impacts owing to the fact that supercritical carbon dioxide is a green solvent. To achieve the best extraction yield, sufficient induction time should be established for PEF extraction and adequate static and dynamic extraction time should be allocated for SFE. The outcomes of the green assessment have manifested that MAE, UAE, PEF and EAE could employ green extraction by using green solvent such as oil and water to replace the use of organic and petroleum-based solvents.